Innovative Therapeutic Approaches in Primary Cutaneous B Cell Lymphoma - Lang, Claudia C. V.; Ramelyte, Egle; Dummer, Reinhard (Frontiers in Oncology, 2020)
BACKGROUND: Primary cutaneous B-cell lymphomas include a infrequent group of non-Hodgkin lymphomas that are limited to skin sites at the time of diagnosis. They comprise roughly 20-25% of all cutaneous lymphomas and are subdivided in marginal zone lymphoma, follicle center lymphoma and diffuse large cell B cell lymphoma, leg type. The first two show a rather good prognosis with a 5 years survival rate >95%. Diffuse large cell B cell lymphoma, leg type carries a serious prognosis. Intravascular large cell B-cell lymphoma is the most infrequent subtype and is not enlarged upon this review.. TOPICAL THERAPY: For solitary, single site disease of marginal zone and follicle center lymphoma topical treatments contain a wide variety of options, which can be suited to the individual needs of affected patients. Even a watchful waiting process is reasonable in specific cases (mostly in marginal zone lymphoma). Surgery, radiotherapy and intralesional agents give a variety to choose from for the individual patient. SYSTEMIC THERAPY: PCFCL barely needs systemic treatment. For extended PCMZL and more importantly DLCBCL, leg type systemic treatment is first choice. Rituximab, a monoclonal antibody against CD20 which elicits its effect through apoptosis, antibody‐dependent cellular cytotoxicity of malignant and normal B cells is an often used systemic treatment for pCBCL. It is sometimes applied in combination with Chemotherapy, but can be applied as monotherapy in PCMZL and PCFCL. Newer options are dacetuzumab, an anti-CD40 monoclonal antibody which binds on certain malignant B cells, checkpoint inhibitors (mainly PD1 and PDL1) and bruton tyrosine kinase antagonists. CONCLUSION: Indolent CBCL are treated with a risk adapted strategy using steroids, RT and interferon 1st. Relapsing cases may profit from rituximab. In aggressive pDLCL radiotherapy alone or polychemo + Rituximab are recommended. New innovations contain the intralesional use of T-VEC and a number of monoclonal antibodies and small molecules in systemic treatments. Due to sparse evidence according pCBCL clinical, multicenter trials should investigate new treatment options and interdisciplinary patient management is recommended.